2017
DOI: 10.1007/s12469-017-0173-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between ad-hoc demand responsive and conventional transit: a simulation study

Abstract: Considering the sprawl of cities, conventional public transport with fixed route and fixed schedule becomes less efficient and desirable every day. However, emerging technologies in computation and communication are facilitating more adaptive types of public transport systems, such as demand responsive transport that operates according to real-time demand. It is crucial to study the feasibility and advantages of these novel systems before implementation to prevent failure and financial loss. In this work, an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Taxi has a small capacity and expensive fare, so it is difficult for taxis to accommodate high demand, and it is also difficult for travelers to use it for regular commuting. DRT has a larger capacity and cheaper fare than a taxi, but it is known that DRT is efficient only when the density of demand is low, making it inappropriate to handle an enormous demand (29)(30)(31)(32)(33). The zonal express is meaningful in this regard: it is useful for O-D pairs with large and simultaneous demands.…”
Section: Practical Suggestionsmentioning
confidence: 99%
“…Taxi has a small capacity and expensive fare, so it is difficult for taxis to accommodate high demand, and it is also difficult for travelers to use it for regular commuting. DRT has a larger capacity and cheaper fare than a taxi, but it is known that DRT is efficient only when the density of demand is low, making it inappropriate to handle an enormous demand (29)(30)(31)(32)(33). The zonal express is meaningful in this regard: it is useful for O-D pairs with large and simultaneous demands.…”
Section: Practical Suggestionsmentioning
confidence: 99%
“…Unlike the conventional fixed-route transit operation problem, which usually deals with four-step issues of (1) network and line design, (2) timetabling, (3) vehicle scheduling, and (4) staff scheduling [13], the DRT plans the routes and schedules of vehicles to match passenger trips and presents vital complexity [14]. The DRT problem has been generalized as a kind of important operation research (OR) problem.…”
Section: A Demand-responsive Transit Operationmentioning
confidence: 99%
“…Demand-responsive transit (DRT) is a form of shared private transport (or quasi-public) for groups travelling where buses alter their routes based on particular demand rather than using fixed routes or timetables. Navidi et al [17] indicated that DRT may improve the mobility and quality of service by reducing the users perceived travel time. Wang et al [18] found that DRT meets the demand of niche markets (e.g., disabled, elderly and live in areas with low population density).…”
Section: B Demand-responsive Transit (Drt)mentioning
confidence: 99%